ФАЗОПОВОРОТНІ ТРАНСФОРМАТОРНІ ПРИСТРОЇ ЗІ ШТУЧНОЮ КОМУТАЦІЄЮ ТИРИСТОРІВ ДЛЯ ПОПЕРЕЧНОГО ТА ПОЗДОВЖНЬО-ПОПЕРЕЧНОГО РЕГУЛЮВАННЯ НАПРУГИ - Жаркін, А.Ф.; Новський , В.О.; Малахатка , Д.О. (Інститут електродинаміки НАН України, Київ, 2014)
The aspects of development of phase-shifting transformer devices (PSTD) circuits for transversal and longitudinal transversal voltage regulation in three-phase system using forced commutation thyristor in switching device are considered. Simulation modes of PSTD for different values of its power under normal and emergency operation system are performed. The research results allow to optimize control algorithms of PSTD switch elements in different operational modes. References 4, figures 3.